2018
DOI: 10.3390/ijms19051404
|View full text |Cite
|
Sign up to set email alerts
|

Human Macrophages Preferentially Infiltrate the Superficial Adipose Tissue

Abstract: Human abdominal subcutaneous adipose tissue consists of two individual layers—the superficial adipose tissue (SAT) and deep adipose tissue (DAT)—separated by the Scarpa’s fascia. The present study focuses on the analysis of morphological and immunological differences of primary adipocytes, adipose-derived stem cells (ASC), and tissue-infiltrating immune cells found in SAT and DAT. Adipocytes and stromal vascular fraction (SVF) cells were isolated from human SAT and DAT specimens and phenotypically characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 39 publications
1
20
1
Order By: Relevance
“…It has been shown before that other disorders of the fat tissue like lipedema do significantly change the yield of cells in SVF isolation compared with healthy individuals . Also, we were able to show different cell yields in a representative sample of the patients in this study when processing superficial abdominal subcutaneous adipose tissue separately from the adipose tissue found deep to Scarpa's fascia as published elsewhere, which proves the versatility of subcutaneous tissue and its compartments on an intraindividual basis. Herein, other authors showed that weight loss is taking place to a different extent in the superficial and deep layers of abdominal subcutaneous fat tissue in bariatric versus lifestyle weight loss .…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…It has been shown before that other disorders of the fat tissue like lipedema do significantly change the yield of cells in SVF isolation compared with healthy individuals . Also, we were able to show different cell yields in a representative sample of the patients in this study when processing superficial abdominal subcutaneous adipose tissue separately from the adipose tissue found deep to Scarpa's fascia as published elsewhere, which proves the versatility of subcutaneous tissue and its compartments on an intraindividual basis. Herein, other authors showed that weight loss is taking place to a different extent in the superficial and deep layers of abdominal subcutaneous fat tissue in bariatric versus lifestyle weight loss .…”
Section: Discussioncontrasting
confidence: 73%
“…Mostly, translational research puts its focus and efforts on applications of multipotent ASCs that are widely known to be important in wound healing . These cells make up for about two‐thirds of the CD45‐negative cells within the SVF, which is thus representative for the amount of ASCs in the tissue, and there is no difference in cell yield between superficial and deep subcutaneous fat layers . Recent literature suggests that the therapeutic effect of ASCs is partially mediated by the secretion of cytokines, and thus they are able to stimulate local fibroblasts of the wound bed to promote wound healing and angiogenesis .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, immunohistochemical analyses in matched human subcutaneous and visceral adipose tissue specimen indicated that -albeit overall TLR9 gene expression is significantly increased in visceral as compared to subcutaneous adipose tissue -there seems to be significant inter-individual variability in TLR9 protein accumulation. Of note, recent reports indicated functionally different compartments within the subcutaneous adipose tissue, which are separated by Scarpia's fascia: The superficial adipose tissue layer had significantly higher numbers of tissue-infiltrating macrophages as compared to the deep adipose tissue layer (Cappellano et al 2018). In this context, our study concentrated on the superficial adipose tissue layer within the subcutaneous adipose tissue.…”
Section: Discussionmentioning
confidence: 75%
“…No change of thickness in men; marginal change in women (<10%) Susceptible to macrophage infiltration (35) Size of human abdominal scWAT adipocytes increases in obese subjects (66, 67)…”
Section: Resistant To Macrophage Infiltration (Crown-like Structures)mentioning
confidence: 99%